Urocortin 1: A putative excitatory neurotransmitter in the enteric nervous system. Issue 10 (20th March 2020) - Yamato, Shigeru; Kurematsu, Ayako; Amano, Tomofumi; Ariga, Hajime; Ando, Tetsuya; Komaki, Gen; Wada, Keiji
Abstract: Background: Urocortin 1 (Ucn1), a stress‐related peptide, is a member of the corticotropin‐releasing factor (CRF) family and acts as a CRF1 receptor agonist. Ucn1 and CRF1 receptor immunoreactivity are present in the enteric nervous system (ENS), and Ucn1 elicits contraction of colonic muscle strips. Considering these findings, we have hypothesized that Ucn1 acts as an excitatory neurotransmitter in the ENS. The present study was conducted to determine whether exogenously applied Ucn1 causes contractions, whether it participates in neurally mediated contraction, and whether it is released from the ENS of the rat colon. Methods: Isometric tension of the rat colonic muscle strips (middle to distal colon) in a longitudinal direction was measured. The effects of Ucn1 on phasic contractions were examined in the absence and presence of antalarmin (CRF1 receptor antagonist), tetrodotoxin (TTX), and atropine. The effects of antalarmin on electrical field stimulation (EFS)‐induced contractions were examined in the absence and presence of atropine. Ucn1 peptide in the bath solution was measured after EFS using an EIA kit. Key Results: Ucn1 caused a significant and dose‐dependent increase in phasic contractions. These effects were completely inhibited by antalarmin, TTX, and atropine. EFS‐induced contractions were inhibited by antalarmin. Atropine markedly reduced EFS‐induced contractions, and antalarmin did not decrease these contractions further. EFS elicited a significant increase in the concentration of Ucn1 in the bath solution, and this increase was completely inhibited by TTX. Conclusions and Inferences: These results suggest that Ucn1 acts as an excitatory neurotransmitter in the ENS enhancing the cholinergic neurotransmission. Abstract : Ucn1 acts as an excitatory neurotransmitter in the ENS enhancing the cholinergic neurotransmission.